Current Ripple Reduction Employing the Reactor of DC–DC Converter to Have Variable Inductance through Magnetic Saturation - Chang-Ho Lee; Tuan-Vu Le; Feel-soon Kang; Sung-Jun Park (IET Electrical Systems in Transportation)
When DC distribution grids with different voltage levels are connected, harmonic currents flow into the grid under light load conditions, which is a significant cause of grid instability. In this paper, we proposed a method to reduce the current ripple at light load by designing a bidirectional DC–DC converter reactor to have an inductance variable according to the load power capacity. The inductance is varied using magnetic saturation and implemented in three ways: two magnetic circuits in one magnetomotive force (MMF) circuit, a single magnetic circuit in one MMF circuit, and two magnetic components with different magnetic permeability in one MMF circuit. The feasibility is verified through simulation and experiments targeting the 750 and 380 V DC grid connection. The operating characteristics and efficiency are compared and analyzed by applying the existing and proposed variable reactor to a bidirectional DC–DC converter.